[PP.36.18]: TREATMENT AND CONTROL OF VARIOUS RISK FACTORS IN HYPERTENSIVE PATIENTS WITH ATRIAL FIBRILLATION. (June 2015) - Kallistratos, M.S.; Poulimenos, L.E.; Karamanou>, A.>; Kouremenos, N.; Koukouzeli, A.; Kontogianis, N.; Tsoukanas, K.; Vergis, K.; Zacharopoulou, I.; Vrakas, S.; Chamodraka, E.; Siama, A.; et al.
Abstract : Objective: Atrial fibrillation (AF) represents the most commonly encountered arrhythmia and hypertension represents a common comorbidity in those patients. Although the coexistence of HTN and AF leads to an abrupt increase of morbidity and mortality only a small fraction of patients have their blood pressure controlled. Moreover, in those patients, assessment of total cardiovascular risk is imperative in order to improve prognosis, while the presence of different risk factors increase the incidence of AF. This study had the purpose to assess treatment and control of different risk factors in hypertensive patients with AF as well as the percentage of patients with INR within target levels. Design and method: We prospectively studied 170 consecutive hypertensive patients with AF (50.89% males) mean age 72 ± 13 years. Patients were on medical therapy dictated by their physicians and blood samples were taken at recruitment. Patients with laboratory exams or arterial blood pressure out of guidelines' range were defined as uncontrolled. Results: 143 (84.6%) patients with AF had a CHADSVASC score > = 2 and only 62 patients (36.7%) were on VKA therapy, while only 28 patients (17.2%) had their INR within target levels. 112 patients (67.47%) had their BP within target levels (<140/90 mmHg). 84 patients were Diabetics and 54 patients (66%) were within the proposed HbA1climits. Among 136 patients with LDL targets for < 115 mg/dl and 35 patients with LDL targets for < 70 mg/dl only 40 patients (29.5%) and 5 patients (14%) respectively had reached their assigned targets. The number of tablets administered as well as the use of fixed combinations was not associated with better implementation of targets proposed by current ESH/ESC guidelines. Conclusions: Reaching of therapeutic targets in different risk factors is challenging since, only a small fraction of patients had reached the guideline-proposed therapeutic targets. In addition only a small fraction of patents in need, receives VKAs and even a smaller percentage is within the proposed therapeutic range.